A physician-based study to assess the prevalence, current treatment standards, and therapy need gaps in the management of irritable bowel syndrome in India - Sheth, Keyur (International Journal of Research in Medical Sciences, 2022)
Background: Irritable bowel syndrome (IBS) is the most common functional gastrointestinal disorder that can significantly affect quality of life. A physician-based survey was conducted to understand the prevalence, current treatment strategies, and gaps in IBS management in India. Methods: A total of 197 physicians participated to complete a questionnaire comprising 36 questions related to the prevalence and current treatment of IBS and assess gaps in its management. Results: Most physicians take a detailed history of the IBS syndrome and association-driven criteria to diagnose IBS. Most physicians reported that >50% of the patients had IBS mixed with anxiety, and most patients with IBS suffered for 2-4 weeks before seeking medical consultation. Most respondents reported that IBS patients took home remedies before consultation. Respondents ranked mebeverine plus chlordiazepoxide, followed by mebeverine monotherapy as preferred treatment for management of IBS symptoms. Mebeverine plus chlordiazepoxide was most preferred for IBS patients with anxiety. More than 70 % of physicians reported that mebeverine and its combination with chlordiazepoxide were efficacious with no adverse events for all subtypes of IBS. Most physicians prescribed probiotics with multiple strains for 2-4 weeks in patients with IBS. Conclusions: IBS is a common gastrointestinal disorder with no apparent diagnosis and management. The survey findings support the use of mebeverine therapy for the management of IBS symptoms.